SUPERVISI AKADEMIK DALAM PENINGKATAN MUTU PEMBELAJARAN DI MADRASAH ALIYAH NEGERI TANAH JAMBO AYE - Jufrizal Jufrizal (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
To make teacher to be more professional workforce, it needs coaching in form of continuous and sustainable supervision. In additions, their professional performance is also need to be paid attention, respected, and acknowledged. In creating the educator’s competency, it needs academic supervision which is aimed to give service and assistance to develop a situation of teaching learning in a classroom. The essence of academic supervision is to coach the teacher to increase the quality of learning process. Therefore teacher is the core in learning which consists of lessons/materials, syllabus, choosing the strategy/method/technique of learning, the use of media and information technology in learning, assessing the process and the result of learning and class action research. Academic supervision in each school is inevitably needed to increase the quality of learning, result of students’ learning, and curriculum in Madrasah Aliyah Negeri Tanah Jambo Aye.